Accountability reporting objectives of Māori organizations. Issue 4 (6th November 2018) - Craig, Russell; Taonui, Rawiri; Wild, Susan; Rodrigues, Lũcia Lima
Abstract : Purpose: This paper aims to highlight the accountability reporting objectives of four Māori-controlled organizations. The examples cited reflect the core values of the indigenous Māori people of New Zealand (Aotearoa) and help demonstrate how these values are manifest in the accountability reporting of Māori-controlled organizations. Design/methodology/approach: Narrative sections of ten annual reports of two small and two large Maori organizations, drawn variously from their financial years ending in the calendar years 2009 to 2014, are read closely. These organizations represent diverse tribal and regional associations in terms of size, scope and structure; and in terms of the business, social and cultural activities they pursue. Findings: Three core Māori values are identified: spirituality ( wairuatanga ); intergenerationalism and restoration ( whakapapa ); and governance, leadership and respect ( mana and rangatiratanga ). The commitment to these values and the way this commitment is reflected in accountability reports of Maori organizations, is presented. Originality/value: The examples provided, and the associated discussion, should help inform reporting initiatives of organizations that are seeking better accountability in terms of their long-term engagement with indigenous communities, the environment and broader society.